Truthfulness in Accounting: How to Discriminate Accounting Manipulators from Non-manipulators - Vladu, Alina Beattrice (Journal of business ethics, 2017)
Accountants preparing information are in a position to manipulate the view of economic reality presented in such information to interested parties. These manipulations can be regarded as morally reprehensible because they are not fair to users, they involve in an unjust exercise of power, and they tend to weaken the authority of accounting regulators. This paper develops a model for detecting earnings manipulators using financial statements’ ratios in a sample of Spanish listed companies. Our results provide evidence that accounting data can be extremely useful in detecting manipulators. This approach can be used by a large category of users of accounting information among which we can cite stock exchange supervisors or investing professionals.